In Situ Cancer Vaccination and Immunovirotherapy Using Oncolytic HSV - Nusrat Jahan; Shanawaz M. Ghouse; Robert L. Martuza; Samuel D. Rabkin (Viruses, 2021)
Herpes simplex virus (HSV) can be genetically altered to acquire oncolytic properties so that oncolytic HSV (oHSV) preferentially replicates in and kills cancer cells, while sparing normal cells, and inducing anti-tumor immune responses. Over the last three decades, a better understanding of HSV genes and functions, and improved genetic-engineering techniques led to the development of oHSV as a novel immunovirotherapy. The concept of in situ cancer vaccination (ISCV) was first introduced when oHSV was found to induce a specific systemic anti-tumor immune response with an abscopal effect on non-injected tumors, in the process of directly killing tumor cells. Thus, the use of oHSV for tumor vaccination in situ is antigen-agnostic. The research and development of oHSVs have moved rapidly, with the field of oncolytic viruses invigorated by the FDA/EMA approval of oHSV talimogene laherparepvec in 2015 for the treatment of advanced melanoma. Immunovirotherapy can be enhanced by arming oHSV with immunomodulatory transgenes and/or using them in combination with other chemotherapeutic and immunotherapeutic agents. This review offers an overview of the development of oHSV as an agent for ISCV against solid tumors, describing the multitude of different oHSVs and their efficacy in immunocompetent mouse models and in clinical trials.